Effect of Carbon Doping on CO2‐Reduction Activity of Single Cobalt Sites in Graphitic Carbon Nitride. Issue 9 (15th June 2021) - Huang, Peipei; Huang, Jiahao; Li, Junying; Zhang, Lei; He, Jie; Caputo, Christine A.; Frenkel, Anatoly I.; Li, Gonghu
Abstract: Single‐atom catalysts have demonstrated interesting activity in a variety of applications. In this study, we prepared single Co 2+ sites on graphitic carbon nitride (C3 N4 ), which was doped with carbon for enhanced activity in visible‐light CO2 reduction. The synthesized materials were characterized with a variety of techniques, including microscopy, X‐ray powder diffraction, UV‐vis spectroscopy, infrared spectroscopy, photoluminescence spectroscopy, and X‐ray absorption spectroscopy. Doping C3 N4 with carbon was found to have profound effect on the photocatalytic activity of the single Co 2+ sites. At relatively low levels, carbon doping enhanced the photoresponse of C3 N4 in the visible region and improved charge separation upon photoactivation, thereby enhancing the photocatalytic activity. High levels of carbon doping were found to be detrimental to the photocatalytic activity of the single Co 2+ sites by altering the structure of C3 N4 and generating defect sites responsible for charge recombination. Abstract : Single‐atom catalysts were prepared by depositing Co 2+ sites on graphitic carbon nitride for use in visible‐light CO2 reduction. Doping carbon nitride with an appropriate amount of carbon significantly improved the photocatalytic activity of the single Co 2+ sites.